OPTIMIZATION OF THE ABSORBENT SOLUTION OF THE HYDROGEN SULFIDE (H2S) GASEOUS POLLUTANT USING ULVAN POLYSACCHARIDES - Coasaca Camacho, María Fátima (2023)
Hydrogen sulfide (H2S) in the environment represents a danger to people's health. Conventional methods for monitoring H2S require absorbent solutions, which usually contains harmful substances such as cadmium sulphate (CdSO4). Constant exposure to cadmium sulphate may cause health damage. In the present work, Ulvan polysaccharides were evaluated as additives in the preparation of absorbent solutions for H2S(g) capture. The resultant Ulvan-based solution featured low content of harmful substances such as cadmium sulphate, sodium hydroxide, and arabinogalactan. The parameters used to validate the performance of the prepared Ulvan-based absorbent solutions included linearity, precision, selectivity, working range, detection limit, quantification limit, robustness, and uncertainty. The relative standard deviation of repeatability (%RSD) was compared to the Horwitz's %RSD. It was found that %RSD was less than Horwitz's %RSD. This showed that measurements were accurate. The linearity of the calibration curve made with the Ulvan-based solutions featured a coefficient of determination (R2) higher than 0.995. The limit of detection (LOD) and quantification (LDQ) values of H2S(g) were 0.13 μg/m3 and 0.26 μg/m3, respectively. Finally, the groups evaluated at different color reaction times were robust. This showed that the determination of H2S(g) content using the Ulvan-based absorbent solution could be performed under normal conditions without affecting the reproducibility of the results. The modified and optimized method with Ulvan polysaccharides complied with the required acceptance parameters proposed. These results showed that Ulvan represents a potential alternative for applications related to detecting polluting gases such as H2S(g).